Anti-allodynic and medullary modulatory effects of a single dose of delta-9-tetrahydrocannabinol (THC) in neuropathic rats tolerant to morphine - Pearl-Dowler, Leora; Posa, Luca; Lopez-Canul, Martha; Teggin, Alexandra; Gobbi, Gabriella (Progress in neuro-psychopharmacology & biological psychiatry, 2023)
Neuropathic pain (NP) is often treated with opioids, the prolonged use of which causes tolerance to their analgesic effect and can potentially cause death by overdose. The phytocannabinoid delta-9-tetrahydrocannabinol (THC) may be an effective alternative analgesic to treat NP in morphine-tolerant subjects. Male Wistar rats developed NP after spared nerve injury, and were then treated with increasing doses of THC (1, 1.5, 2, 2.5, and 5 mg/kg, intraperitoneally), which reduced mechanical allodynia at the dose of 2.5 and 5 mg/kg. Another group of NP rats were treated with morphine (5 mg/kg, twice daily for 7 days, subcutaneously), until tolerance developed, and on day 8 received a single dose of THC (2.5 mg/kg), which significantly reduced mechanical allodynia. To evaluate the modulation of THC in the descending pain pathway, in vivo electrophysiological recordings of pronociceptive ON cells and antinociceptive OFF cells in the rostroventral medulla (RVM) were recorded after intra-PAG microinjection of THC (10 μg/μl). NP rats with morphine tolerance, compared to the control one, showed a tonic reduction of the spontaneous firing rate of ON cells by 44%, but the THC was able to further decrease it (a hallmark of many analgesic drugs acting at supraspinal level). On the other hand, the firing rate, of the antinociceptive OFF cells was increased after morphine tolerance by 133%, but the THC failed to further activate it. Altogether, these findings indicate that a single dose of THC produces antiallodynic effect in individuals with NP who are tolerant to morphine, acting mostly on the ON cells of the descending pain pathways, but not on OFF cells. •Delta-9-tetrahydrocannabinol (THC) reduces mechanical allodynia in neuropathic rats tolerant to morphine.•This effect is mostly mediated by THC action on the ON cells of the RVM in the descending modulatory pathway.•THC may be a promising tool to treat neuropathic pain in the context of the opioid crisis.